Psychosocial determinants of adolescent romantic relationship in malaysia: social media use, pornography surfing, sexual and reproductive health knowledge, and depression - Mud Shukri, Muhammad Ikhwan; Baharom, Anisah (Public Library of Science, 2023)
It is socially natural that adolescents engage in romantic relationship. However, there are negative health implications when they are not properly monitored and guided. The engagement in unsafe sexual practices has been reported to cause various adverse health and social implications affecting Malaysian adolescents. To date, why adolescents engage in romantic relationship has remained understudied. Prior studies on adolescent romantic relationship mainly focused on the western context. Hence, the reported findings are deemed not applicable for the Malaysian population. There are insufficient data on the prevalence and determinants of adolescent romantic relationship within the Malaysian context. Thus, the current study aimed to identify the prevalence and determinants of romantic relationship among adolescents in Seremban, Negeri Sembilan, Malaysia. Adopting a cross-sectional research design, this study’s self-administered questionnaire survey, which was conducted from 25 May 2021 to 5 June 2021 in residential areas that were part of the “Healthy Community Empowers the Nation” programme (KOSPEN), involved 396 adolescents who fulfilled the study’s selection criteria. In terms of age, the respondents were of between 14 and 19 years old, with median age (IQR) of 19 (2). Adolescent romantic relationship in this study recorded prevalence of 24.1%, which was comparatively lower than that of the western countries. The results further revealed social media use (AOR: 2.162, 95% CI: 1.202–3.888, p = 0.01), pornography website surfing (AOR 2.748, 95% CI: 1.517–4.977, p = 0.001), poor SRH knowledge (AOR: 3.885, 95% CI: 2.144–7.040, p < 0.001), and depression (AOR: 2.830, 95% CI: 1.323–6.055, p = 0.007) as significant determinants of adolescent romantic relationship. Thus, this study demonstrated the significant role of social media use, pornography website surfing, SRH knowledge, and depression on adolescent romantic relationship. Further longitudinal studies to investigate the temporal relationships between depression and romantic relationship are recommended. The highly significant association between SRH knowledge and romantic relationship in this study suggests that strategies on improving the level of SRH knowledge among adolescents should be prioritised.